Satisfaction of Kolej GENIUS Insan Students in Learning History Subject - Muhammad Alif Safwan Azlan; Siti Munirah Mohd; Shafinah Kamarudin; Nurhidaya Mohamad Jan; Mahiz Spawi (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia